La gestión de compras en el proceso de conversión de una empresa panificadora a retail, en el contexto de pandemia. Lima, 2020-2021 - Arenas Pinillos, Belén (2023)
The main goal of this research is to determine the importance of the constant change and adaptation in companies during times of uncertainty or crisis through the study and analysis of a particular case as an example. To achieve this, the procurement department in a company that operates in the pastry and cafeteria industry was studied during the adaptation process it had to go through as the result of an unpredictable event such as the COVID-19 pandemic. It was carried out with a qualitative approach, with both descriptive and explanatory scope that seek to expose the causes of an specific problem. Also, with a non-experimental design due to being based on existing theories. When studying a particular case and taking Hernández and Mendoza as a reference, it was determined that the study methodology used would be the case study. For sample questions, in-depth interviews were conducted to five employees (3 managers included) of the company, which allowed the obtaining data with a holistic view of the company. To meet the objectives set, two variables were determined, from which dimensions were broken down, which were the subject of study and analysis. Regarding theoretical bases, information was obtained from different sources, books and authors that support the information obtained through the interviews. Among the conclusions raised, it is determined the importance of constant evolution and innovation to survive in environments filled with uncertainty and chaos such as the COVID-19 Pandemic.